Effects of Intervention on Home-Based Environmental Counselling for Children with Severe Allergic Diseases (Medico Legal Update, 2020)
Background/Objectives: Home-based environmental management is the key to managing allergic diseases. This study identified the effects of environmental counseling intervention in children with atopic dermatitis and respiratory diseases.Methods/Statistical analysis: The participants were 198 children with allergic diseases who participated in the study in 2016. In 2017, 66 children with severe allergic diseases in a follow-up study were selected. We ultimately analyzed the effect of environmental counseling in 26 children. To assess the effect of the intervention, the research team conducted a pre-test (baseline) and post-test (follow-up) twice. Trans-epidermal water loss (TEWL) and scoring atopic dermatitis (SCORAD) index were used to assess atopic dermatitis (AD) and forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), immunoglobulin E (IgE), and eosinophil counts were used to assess respiratory diseases.Findings: In children with AD, the baseline and follow-up SCORAD index values were 40.33 and 31.15 points, respectively. In children with respiratory diseases, the baseline and follow-up FEV1 values were 77.77 and 87.53 points, respectively; baseline and follow-up FVC values were 81.38 and 95.54 points, respectively; baseline and follow-up IgE values were 520.86 and 481.37 points, respectively; and baseline and follow-up eosinophil values were 4.97 and 4.42 points, respectively. Thus, home-based environmental counseling decreased FEV1 and FVC values.Improvements/Applications: Patients with respiratory diseases treated with home-based environmental counseling exhibited positive changes in FEV1 and FVC values. Home-based indoor environmental counseling is regularly needed to manage respiratory diseases. The parents of children with respiratory diseases must try to minimize their exposure to harmful substances indoors